KINETIC MECHANISM REDUCTION FOR METHYL FORMATE THROUGH DEPTH FIRST SEARCH AND SENSITIVITY ANALYSIS - Padilha, F. R. R.; Minuzzi, F. C. C.; De Bortoli, A. L.; Pinho, J. M. (Revista Interdisciplinar de Pesquisa em Engenharia, 2017)
Biodiesel has been considered the most promising fuel to replace part of the fossil diesel consumed worldwide, since it is a renewable and biodegradable fuel. There is the need of reduced kinetic mechanisms for the effective numerical simulation of these fuels. In this way, the aim of this work is the development of a reduced mechanism of moderate stiffness for Methyl Formate (MF). MF is not indicated as a biodiesel surrogate due to its higher reactivity, but its study enables to isolate the role of each ester in combustion processes. So, based on a detailed mechanism consisting of 950 reactions and 176 species, Directed Relation Graph with Depth First Search and Sensitivity Analysis are employed to obtain a small mechanism with 43 reactions and 23 species for MF. This mechanism has reasonable accuracy compared to the full mechanism and decreases the computational cost for obtaining the solution of the reactive flow.